2018
DOI: 10.2478/anre-2018-0032
|View full text |Cite
|
Sign up to set email alerts
|

Association of socio-culture factors with disordered eating behavior: An empirical study on urban young girls of West Bengal, India

Abstract: A shift towards the concept of thin body image is occurring among the urban girls, as an outcome of mass media exposure. A large section of the girls are involved in attaining thin body image which at times develops dissatisfaction over body weight. Body weight dissatisfaction gives rise to the development of body weight concern and disordered eating behavior. The present research aimed to find out the association of socio-cultural factors with disordered eating behavior among a group of urban girls. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…Socio-economic factors affect many components of the standard of living, including quality and quantity of nutrition or the distribution of goods per person (e.g. Bharthi et al 2017;Ganguly et al 2018). Our ANOVA results confirmed the impact of socio-economic factors in causing the diverse average age of menarche.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Socio-economic factors affect many components of the standard of living, including quality and quantity of nutrition or the distribution of goods per person (e.g. Bharthi et al 2017;Ganguly et al 2018). Our ANOVA results confirmed the impact of socio-economic factors in causing the diverse average age of menarche.…”
Section: Discussionsupporting
confidence: 75%
“…Among environmental factors nutritional status and socioeconomic status are the most frequently cited (e.g. Berkey et al 2000;Junqueira et al 2003;Ellis 2004;Malina et al 2004;Ellis and Essex 2007;Bralić et al 2012;Krzyżanowska et al 2016;Bharthi et al 2017;Ganguly et al 2018). Results of earlier research on girls from Central India have shown that they attain menarche at the mean age of 14 years, with wide variations: 10-20 years, only 13% of studied females attained menarche up to 12 years, while almost 50% of the group between 14-15 years (see: Liczbińska et al 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the medium correlations with the CFRS were expected, given that this scale focuses on desire to change weight and shape. These findings add to research which has identified an association between disordered eating and body dissatisfaction among girls in India (Ganguly et al, 2018; Singh Mannat et al, 2016). The EDE‐Q and its subscales also showed medium correlations with the Internalization‐General subscale, which was unsurprising, due to the identification of internalization as a prospective risk factor among adolescents in high‐income countries (Dakanalis et al, 2015; Wichstrøm, 2000).…”
Section: Discussionsupporting
confidence: 74%
“…However, growing research suggests that disordered eating is a global issue (Pike & Dunne, 2015; van Hoeken, Burns, & Hoek, 2016). In India (Sagar et al, 2020; Vaidyanathan, Kuppili, & Menon, 2019), threshold eating disorders (e.g., anorexia nervosa) and their clinical features are prevalent among both adults (Jugale, Pramila, Murthy, & Rangath, 2014; Ramaiah, 2015; Vijayalakshmi et al, 2017) and adolescents (Ganguly, Roy, & Mukhopadhyay, 2018; Mammen, Russell, & Russell, 2007; Singh Mannat, Parsekar, & Bhumika, 2016). Research conducted among a convenience sample of 454 medical and nursing students (both men and women) found that 41–48% reported engaging in binge eating; with 25–47% of the sample excessively exercising to lose weight (Vijayalakshmi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation